Funduscopic and Transcranial Doppler Profile of the Ophthalmic Artery in Stroke Patients with Hypertensive Retinopathy - Dini Adriani; Eva Dewati; Freddy Sitorus; Ni Nengah Rida Ariani; Dinda Diafiri; Tiara Kasih; Mohammad Kurniawan (Journal of Neurointervention and Stroke, 2025)
Highlight: Hypertensive retinopathy may predict stroke risk TCD may complement funduscopy in stroke with HR ABSTRACT Introduction: Hypertensive retinopathy (HR) is a manifestation of chronic vascular damage and is increasingly recognized as a predictor of stroke. Funduscopy and Transcranial Doppler (TCD) examination of the ophthalmic artery may offer non-invasive insight into cerebrovascular health. Objective: To describe the demographic, funduscopic, and ophthalmic artery hemodynamic profiles in stroke patients with hypertensive retinopathy using Transcranial Doppler. Method: A cross-sectional descriptive study was conducted from May 2022 to May 2025 at Cipto Mangunkusumo National Hospital, involving 67 ischemic stroke patients with HR. Retrospective data were collected from medical records, including sociodemographics, fundus classification based on Wong and Mitchell, and Pulsatility Index (PI) values of the ophthalmic artery from TCD. Result: Mild hypertensive retinopathy is prevalent in ischemic stroke patients, and elevated ophthalmic artery PI values are suggestive of small-vessel disease. Conclusion: Funduscopy and TCD can be complementary tools in evaluating stroke risk in hypertensive.